Multifocal epilepsy in children is associated with increased long-distance functional connectivity: An explorative EEG-fMRI study. (November 2018) - Siniatchkin, Michael; Moehring, Jan; Kroeher, Bianca; Galka, Andreas; von Ondarza, Gisela; Moeller, Friederike; Wolff, Stephan; Tagliazucchi, Enzo; Steinmann, Elisabeth; Boor, Rainer; Stephani, Ulrich
Abstract: Objective: Multifocal epileptic activity is an unfavourable feature of a number of epileptic syndromes (Lennox-Gastaut syndrome, West syndrome, severe focal epilepsies) which suggests an overall vulnerability of the brain to pathological synchronization. However, the mechanisms of multifocal activity are insufficiently understood. This explorative study investigates whether pathological connectivity within brain areas of the default mode network as well as thalamus, brainstem and retrosplenial cortex may predispose individuals to multifocal epileptic activity. Methods: 33 children suffering from multifocal and monofocal (control group) epilepsies were investigated using EEG-fMRI recordings during sleep. The blood oxygenated level dependent (BOLD) signal of 15 regions of interest was extracted and temporally correlated (resting-state functional connectivity). Results: Patients with monofocal epilepsies were characterized by strong correlations between the corresponding interhemispheric homotopic regions. This pattern of correlations with pronounced short-distance and weak long-distance functional connectivity resembles the connectivity pattern described for healthy children. Patients with multifocal epileptic activity, however, demonstrated significantly stronger correlations between a large number of regions of the default mode network as well as thalamus and brainstem, with a significant increase in long-distance connectivity compared to children with monofocal epileptic activity. In the group of patients with multifocal epilepsies there were no differences in functional connectivity between patients with or without Lennox-Gastaut syndrome. Conclusion: This explorative study shows that multifocal activity is associated with generally increased long-distance functional connectivity in the brain. It can be suggested that this pronounced connectivity may represent either a risk to pathological over-synchronization or a consequence of the multifocal epileptic activity. Highlights: The pattern of functional connectivity in monofocal epilepsies resemble thus of the healthy subjects. Children with multifocal epilepsies and a higher seizure frequency are characterized by an increased functional connectivity. There is no differences in functional connectivity between patients with or without Lennox-Gastaut syndrome.